In ovulo rescue of hybrid embryos in flame seedless grapes - influence of pre-bloom sprays of benzyladenine - Bharathy, P. V.; Karibasappa, G. S.; Patil, S. G.; Agrawal, Dinesh C. (Scientia Horticulturae, 2005)
Based on the theory that cytokinins are known to increase the sink strength of seeds for assimilates, the present investigation was carried out to study the influence of pre-bloom and bloom time sprays of benzyladenine (BA) on embryo recovery, germination and plant development in Flame Seedless grape variety by using in ovulo rescue methods. The combined effect of pollen parent type and sprays of BA drastically improved these parameters and the embryo recovery was more than doubled in all the crosses, except in cross FS x Concord. Also, germination of embryos was higher when BA sprays were given. Recovery of embryos and growth depended on BA treatment and the pollen parent types. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: benzyladenine; flame seedless; in ovulo embryo rescue; interspecific hybridization; Vitis spp.

Grapevine DNA polymorphisms revealed by microsatellite-derived markers from soybean and rice - Agrawal, Dinesh C.; Topfer, R.; Zyprian, E. (Vitis, 2006)
We report detection of DNA polymorphisms in grapevine by the use of microsatellite-flanking primer pairs from soybean and rice. These "cross species" microsatellite-derived markers were checked for their inheritance patterns in controlled grapevine crosses. They produced multiple bands that segregated and can be scored as individual genetic markers of dominant type. Employed in genetic mapping studies they offer advantages such as improved reproducibility in comparison to commonly used multi-locus marker systems like RAPDs and AFLPs.
Keywords: 1; 3-dipolar addition; pyrazoles; regiospecific reaction; sydnones

Synergistic effect of CPPU and benzyladenine on embryo rescue in six. stenospermocarpic cultivars of grapevine - Nookaraju, A.; Barreto, M. S.; Karibasappa, G. S.; Agrawal, Dinesh C. (Vitis, 2007)
In ovulo/embryo culture technique has been used to recover hybrids from seedless grapevines. The present investigation was carried out to study the influence of pre-bloom sprays of N-(2-chloro-4-pyridyl)-N'-phenylurea (CPPU) - a synthetic cytokinin, and N-6-benzyladenine (BA) supplemented in culture media on embryo recovery in six stenospermocarpic grapevine cultivars. The results showed synergistic effect of CPPU and BA on embryo recovery. Though a CPPU spray alone increased embryo recovery in four out of six cultivars tested, the efficiency was enhanced several fold on culture of excised ovules on media supplemented with BA. The percentage of embryo recovery also depended on BA concentration and varied among six cultivars indicating a genotypic influence as well. Germination percentage of rescued embryos varied among the six cultivars and mostly corresponded with embryo recovery. Germinated embryos developed into normal plantlets. Present study demonstrates that spraying of panicles with CPPU and incorporation of BA in the ovule culture medium can enhance the embryo recovery in stenospermocarpic cultivars of grapevine.
Keywords: benzyladenine; CPPU; embryo rescue; seedless grapes

Cellular polyamines influence maturation and germination of somatic embryos from pro-embryonal masses of two grapevine cultivars - Nookapaju, A.; Barreto, M. S.; Agrawal, Dinesh C. (Vitis, 2008)
Somatic embryos of grapevine multiply repeatedly and often fail to mature and germinate due to factors like dormancy and embryo teratology. The present investigation was carried out to improve the maturation and germination of somatic embryos from pro-embryonal masses (PEM) of 2A-Clone and `Crimson Seedless', two seedless grapevine cultivars. Also, the aim was to study a correlation between cellular and residual polyamine (PA) levels in PEM and culture media. The efficiency of maturation and germination of embryos from PEM varied significantly between the two cultivars and depended on incubation period and type of PAs in the medium. HPLC analysis showed that higher levels of cellular putrescine in PEM had correlation with maturation and germination percentages in both cultivars. The levels of three PAs depleted in the media rapidly indicating its uptake by PEM. Of the three PAs, putrescine (PUT) was the most effective and resulted in 100.0 or 92.0 % maturation at 14 d or 30 d in 2A-Clone or `Crimson Seedless', respectively. The maximum germination of somatic embryos was recorded with PUT at 14 d or 21 d in 2A-Clone or `Crimson Seedless', respectively.
Keywords: germination; Grapevine; maturation; polyamines; `2A-Clone'; `Crimson Seedless'

High frequency occurrence of single cotyledonary embryo morphotype and repetitive somatic embryogenesis in `Thompson Seedless' crossed with seven grapevine male parents - Bharathy, P. V.; Agrawal, Dinesh C. (Vitis, 2008)
Direct somatic embryogenesis was observed in zygotic embryos rescued from intra- and inter-specific crosses between `Thompson Seedless' and seven male parents of grapevine when the embryos were cultured on Woody Plant Medium (WPM) supplemented with benzyladenine (1 mu M). Repetitive somatic embryogenesis occurred on the same medium, which also supported a high percentage of embryo maturation, germination and plantlet development. The cultures retained embryogenic potential for more than two years. We observed a high frequency occurrence of mono-cotyledonous embryo morphotype and other morphological variations in somatic embryos of all the crosses. The percentage of embryos having mono-, di-, tri-, multiple and abnormal cotyledons varied among the crosses. The overall percentage of monocot embryos was 35.50 %, as against 38.64 % of dicot embryos, while the germination rates for mono- and dicot- embryos were 24.44 % and 24.15 %, respectively. Shoot development was poor in tri- and multiple-cotyledonary embryos, while there was no shoot formation in abnormal embryos. We assume that the relatively high occurrence of single cotyledonary morphotype, may be due to the repetitive exposure of embryogenic tissues to a medium containing benzyladenine.
Keywords: cotyledon; Grapevine; somatic embryo; Vitis

Variability among vitis vinifera cultivars to in vitro propagation - Barreto, M. S.; Nookaraju, A.; Joglekar, A. M.; Karibasappa, G. S.; Agrawal, Dinesh C. (Proceedings of the International Symposium on Grape Production and Processing, 2008)
Response of grapevines to tissue culture has been reported to be genotype dependent, hence it becomes imperative to optimize culture conditions for newly developed varieties or cultivars, needing a large scale planting but availability of sufficient planting stock is a constraint. In the present study, conditions for in vitro propagation of six popular table grape cultivars have been standardized. Single node stem segments of cultivars 2A-Clone of Thompson Seedless, Red Globe, Crimson Seedless, Thompson Seedless, Flame Seedless and Italia cultured on ten different basal media showed varied percentages of bud break and morphogenetic responses. The percentage of bud break varied among the six cultivars. Direct rooting at basal ends of single node segments was observed in all the cultivars except in Italia. Woody plant medium induced the highest response and Eriksson medium the least in all the cultivars tested. Rooted nodal segments with shoots in axils could be established into whole plants on potting. Six cultivars showed different optimum concentrations of growth regulators for induction of maximum number of multiple shoots in both primary as well as secondary nodal segments. Shoot proliferation could be enhanced by several fold in the majority of cultivars on culture of initial shoot clumps to glass bottles instead of culture tubes. Six cultivars showed significant differences in optimum requirement of nutrients and growth regulators for shoot elongation, in vitro and ex vitro rooting and survival rate. Tissue culture plants of all the six cultivars could establish successfully in a greenhouse.
Keywords: basal media; Grapevine; growth regulators; micropropagation; Tissue culture; Vitis

Enhanced tolerance of transgenic grapevines expressing chitinase and beta-1,3-glucanase genes to downy mildew - Nookaraju, Akula; Agrawal, Dinesh C. (Plant Cell Tissue and Organ Culture, 2012)
An Agrobacterium-mediated transformation protocol for grapevine cv. Crimson Seedless using sonication and anti-necrotic agents has been optimized, and transgenic lines carrying wheat chitinase and beta-1,3-glucanase genes have exhibited enhanced tolerance to downy mildew incited by Plasmopara viticola. cDNA clones encoding chitinase and beta-1,3-glucanase have been isolated from a cDNA library, constructed from scab-infected Sumai-3 wheat, and introduced into a plant cloning vector to generate the plasmids pCAMBAR.chi.11 and pCAMBAR.638. Embryogenic cultures, established from in vitro-derived leaves, of Crimson Seedless were used as explants for Agrobacterium tumefaciens-mediated transformation studies. Sonication of somatic embryos in a bacterial suspension of A. tumefaciens and incorporation of anti-necrotic agents in the co-cultivation medium significantly enhanced transformation efficiency. Transformation efficiency of embryos with either chitinase or beta-1,3-glucanase gene was highest when embryos were suspended in a bacterial cell suspension at 0.5 OD600 and sonicated for 2 or 3 s at 60 kHz. Transformation efficiency with chitinase was highest on incorporation of 2 or 3 mg l(-1) phenylalanine, 1 or 2 mg l(-1) silver nitrate or 400 mg l(-1) l-cysteine in co-cultivation medium while incorporation of 20 mg l(-1) sodium thiosulphate produced highest transformation efficiency with beta-1,3-glucanase. Confirmed transgenic grapevine lines harboring anti-fungal genes exhibited higher levels of chitinase and beta-1,3-glucanase transcripts as well as enzymatic activities. Moreover, transgenic lines showed enhanced tolerance to P. viticola infection following detached leaf assays.
Keywords: Agrobacterium tumefaciens; Anti-oxidants; Downy mildew tolerance; Grapevine; Sonication

Genetic homogeneity of in vitro raised plants of grapevine cv. crimson seedless revealed by ISSR and microsatellite markers - Nookaraju, A.; Agrawal, Dinesh C. (South African Journal of Botany, 2012)
The present study was conducted to test the clonal homogeneity of six month old tissue culture raised plants of grapevine cv. Crimson Seedless using Inter Simple Sequence Repeat (ISSR) and Simple Sequence Repeat (SSR) markers. Visible assessment of these in vitro raised plants maintained in polyhouse did not show any morphological differences among themselves. However, to test the genetic homogeneity of these plants, we screened 50 ISSR primers out of which, 22 primers produced scorable and repeatable bands. These 22 primers were used further for assessing genetic homogeneity of in vitro raised plants of Crimson Seedless. These 22 ISSR primers generated 134 distinct band classes with a total of 3216 scorable bands. All the primers showed uniform banding pattern for all the in vitro raised plants and the mother plant. In case of 5 SSR primers (VS I, VVMD5, VVS2, VMCNG4c8 and VVMD31) used, a total of 288 scorable bands were obtained. The allele sizes ranged from 98 to 254 bp. Allelic composition of 23 in vitro raised plants and the mother plant at 5 SSR loci did not show any polymorphism. The results of the two marker systems in the present study revealed the genetic uniformity among the in vitro raised plants demonstrating the reliability of in vitro propagation system used for the cultivar. (C) 2011 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Allele composition; Clonal fidelity; Inter Simple Sequence Repeats; Monomorphic bands; Tissue culture; Vitis vinifera L.

Use of amino acids for a highly efficient somatic embryogenesis in grapevine `Crimson Seedless' - Nookaraju, A.; Agrawal, Dinesh C. (Vitis, 2013)
Somatic embryogenesis influenced by growth regulators and amino acids was studied in in vitro leaves of grapevine `Crimson Seedless'. In vitro leaves of the cultivar were collected from multiple shoot cultures maintained on Murashige and Skoog's (MS) basal medium supplemented with 9 mu M N-6-benzyladenine (BA). Among the growth regulators used, BA at 4.5 mu M induced higher embryogenic response producing more number of somatic embryos per explant. This response was increased with the addition of 5 mu M naphthoxyl-acetic acid (NOA) to 1/2 MS containing 4.5 mu M BA. Further, supplementation of amino acids in the callus induction medium significantly improved the embryogenic response of in vitro leaves. The higher number of explants showing somatic embryo production (55.3 %) and higher number of somatic embryos per explant (15.5 per explant) were recorded with the supplementation of 5 mM phenylalanine to callus induction medium. Primary somatic embryos showed repetitive embryogenesis on % MS medium devoid of growth regulators. Plantlets derived from somatic embryos were transferred to soil-sand-peat mixture (1:1:1 v/v) and hardened plantlets were established in greenhouse with 90 % survival. This somatic embryogenesis system has been successfully used for Agrobacterium-mediated transformation studies in `Crimson Seedless' in our laboratory. To our knowledge, this is the first report on the use of amino acids for the high efficient somatic embryogenesis in grapevine.
Keywords: Amino acids; somatic embryogenesis; Vitis vinifera L.; `Crimson Seedless'

Leucaena sp recombinant cinnamyl alcohol dehydrogenase: purification and physicochemical characterization - Patel, Parth; Gupta, Neha; Gaikwad, Sushama M.; Agrawal, Dinesh C.; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2014)
Cinnamyl alcohol dehydrogenase is a broad substrate specificity enzyme catalyzing the final step in monolignol biosynthesis, leading to lignin formation in plants. Here, we report characterization of a recombinant CAD homologue (LICAD2) isolated from Leucaena leucocephala. LICAD2 is 80 kDa homodimer associated with non-covalent interactions, having substrate preference toward sinapaldehyde with K-cat/K-m of 11.6 x 10(6) (M-1 s(-1)), and a possible involvement of histidine at the active site. The enzyme remains stable up to 40 C, with the deactivation rate constant (K-d*) and half-life (t(1/2)) of 0.002 and 5 h, respectively. LICAD2 showed optimal activity at pH 6.5 and 9 for reduction and oxidation reactions, respectively, and was stable between pH 7 and 9, with the deactivation rate constant (K-d*) and half-life (t(1/2)) of 7.5 x 10(-4) and 15 h, respectively. It is a Zn-metalloenzyme with 4 Zn2+ per dimer, however, was inhibited in presence of externally supplemented Zn2+ ions. The enzyme was resistant to osmolytes, reducing agents and non-ionic detergents. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cinnamyl alcohol dehydrogenase (CAD); Metalloenzyme; Substrate specificity

c Squalene synthase gene from medicinal herb bacopa monniera: molecular characterization, differential expression, comparative modeling, and docking studies - Vishwakarma, Rishi K.; Patel, Krunal; Sonawane, Prashant; Kumari, Uma; Singh, Somesh; Ruby; Shakeel Abbassi; Agrawal, Dinesh C.; Tsay, Hsin-Sheng; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2015)
The widespread pharmaceutically important triterpenoid saponins are synthesized via isoprenoid pathway. The formation of squalene is the key regulatory point in triterpene biosynthesis, catalyzed by squalene synthase (SQS). The present study deals with the detailed characterization of SQS by molecular, biochemical, and computational means from Bacopa monniera, an immensely important medicinal plant rich in triterpenoid saponin, bacosides. A full-length SQS gene was isolated from B. monniera, characterized as B. monniera squalene synthase (BmSQS) (1242 bp) encoding 414 amino acids. Deduced amino acid sequence of BmSQS showed highly conserved consensus aspartate-rich motifs (DXXXD) and catalytic site residues. Phylogenetic analysis showed that BmSQS belongs to dicot group having closest relationship with Salvia miltiorrhiza. Semiquantitative and real-time PCR studies showed that the BmSQS messenger RNA (mRNA) expression level was higher in vegetative parts (roots) as compared to floral parts. Methyl jasmonate induces the BmSQS mRNA expression in all tissues tested, while salicylic acid, cold, and salt induce much higher expression in roots. Homology modeling and docking simulations of BmSQS showed the pivotal roles of Asp77, Asp81, Asp213, Asp217, and Tyr168 in catalysis.
Keywords: Abiotic stress; Bacopa monniera; Comparative modeling and docking; Differential expression; Isoprenoid pathway; Squalene synthase

Insights into the unfolding pathway and identification of thermally sensitive regions of phytase from aspergillus niger by molecular dynamics simulations - Kumar, Kapil; Patel, Krunal; Agrawal, Dinesh C.; Khire, Jayant Malhar (Journal of Molecular Modeling, 2015)
Thermal stability is of great importance in the application of commercial phytases. Phytase A (PhyA) is a monomeric protein comprising twelve alpha-helices and ten beta-sheets. Comparative molecular dynamics (MD) simulations (at 310, 350, 400, and 500 K) revealed that the thermal stability of PhyA from Aspergillus niger (A. niger) is associated with its conformational rigidity. The most thermally sensitive regions were identified as loops 8 (residues 83-106), 10 (161174), 14 (224-230), 17 (306-331), and 24 (442-444), which are present on the surface of the protein. It was observed that solvent-exposed loops denature before or show higher flexibility than buried residues. We observed that PhyA begins to unfold at loops 8 and 14, which further extends to loop 24 at the C-terminus. The intense movement of loop 8 causes the helix H2 and beta-sheet B3 to fluctuate at high temperature. The high flexibility of the H2, H10, and H12 helices at high temperature resulted in complete denaturation. The high mobility of loop 14 easily transfers to the adjacent helices H7, H8, and H9, which fluctuate and partially unfold at high temperature (500 K). It was also observed that the salt bridges Asp110-Lys149, Asp205-Lys277, Asp335-Arg136, Asp416-Arg420, and Glu387-Arg400 are important influences on the structural stability but not the thermostability, as the lengths of these salt bridges did not increase with rising temperature. The salt bridges Glu125-Arg163, Asp299-Arg136, Asp266-Arg219, Asp339-Lys278, Asp335-Arg136, and Asp424-Arg428 are all important for thermostability, as the lengths of these bridges increased dramatically with increasing temperature. Here, for the first time, we have computationally identified the thermolabile regions of PhyA, and this information could be used to engineer novel thermostable phytases. Numerous homologous phytases of fungal as well as bacterial origin are known, and these homologs show high sequence similarity. Our findings could prove useful in attempts to increase the thermostability of homologous phytases via protein engineering.
Keywords: Conformational dynamics; Molecular dynamics simulations; PhytaseA; Structurally weak regions; Thermostability